Concentration of insecticides cypermethrin isomer in total suspended particulate in air of Cameron Highlands, Pahang, Malaysia : Kepekatan insektisid isomer cybermetrin pada zarahan termendap di udara Cameron Highlands, Pahang, Malaysia - Norela Sulaiman,; Toh, Lee Fong,; Hazzila Abdul Samat,; Ismail Sahid,; Rozali Othman,; Maimon Abdullah, (Universiti Kebangsaan Malaysia, 2007)
This study was carried out to determine the concentrations of cypermethrin in total suspended particulate in air in several farming areas of Cameron Highlands. Samples of total suspended particulate were collected using a high volume air sampler (Model Graseby) from six different sampling sites around Cameron Highlands. Laboratory analysis of total suspended particulate was conducted by the standard method. High dosages of cypermethrin were used by farmers in the dry season. Results of the study showed that the concentrations of cypermethrin in total suspended particulate in the air samples were higher during the dry season (May-July 2004) compared to the rainy season (September-October 2004). There was a significant positive correlation between the concentrations of cypermethrin and total suspended particulate (p<0.05).